Penerapan Pembelajaran Discovery Learning untuk Meningkatkan Kemampuan Komunikasi Matematis dan Keterampilan Kolaborasi Siswa - Zahra Zakiyatussoliha; Mustika Esa Fitri (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the effect of implementing learning using Discovery Learning model on student’s mathematical communication and collaboration skills. This research is quantitative research using a one-group pretest-postest design. This study was conducted in class VIII B of SMP Muhammadiyah 3 Depok in the 2022/2023 academic year. Instrument of this research is test and non-test. The test instrument is pretest and posttest on mathematical communication and the non-test instrument is a questionnaire on student collaboration skills. The data analysis techniques used in this study involved descriptive statistical analysis, normality tests, and paired t-tests which were used to analyze the influence of students' mathematical communication skills and collaborative skills. The results of the research show that Discovery Learning has a positive influence on students' mathematical communication abilities and collaboration skills and can improve students' mathematical communication skills, which reach the medium category (N-gain= 0.62), and collaboration skills, which reach the medium category (N-gain= 0 .63). This study shows that the Discovery Learning model can be used as an alternative for learning mathematics to improve students' mathematical communication skills and collaboration skills effectively.